2023
DOI: 10.1177/17531934231187830
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a virtual fracture care protocol in non-operative treatment of adult patients with a distal radial fracture

Gijs J. A. Willinge,
Jelle F. Spierings,
Ton Weert
et al.

Abstract: This study aimed to determine the effects of virtual fracture care (VFC) on secondary healthcare utilization in non-operative treatment of adult patients with a distal radial fracture. A retrospective cohort study was performed, including those who received non-operative treatment without VFC (pre-VFC) and with VFC (VFC). Outcomes included secondary healthcare utilization, calculated treatment costs, emergency department (ED) reattendances and complication rates. In total, 88 pre-VFC and 99 VFC patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As our study's observed results are greater than just a shift to remote care, we believe these stem from aspects unaffected by the pandemic, such as organized supervision, multidisciplinary planning, and treatment uniformity. Additionally, a prior study comparing a similar VFC review workflow to pre-VFC treatment during the same COVID period in two hospital sites yielded positive results favoring the VFC review, reinforcing the attribution of outcomes to the VFC review workflow ( 42 ). Finally, the reduction of follow-up appointments, improved allocation of tasks and shift to remote care following VFC review suggests a concomitant cost reduction.…”
Section: Discussionmentioning
confidence: 75%
“…As our study's observed results are greater than just a shift to remote care, we believe these stem from aspects unaffected by the pandemic, such as organized supervision, multidisciplinary planning, and treatment uniformity. Additionally, a prior study comparing a similar VFC review workflow to pre-VFC treatment during the same COVID period in two hospital sites yielded positive results favoring the VFC review, reinforcing the attribution of outcomes to the VFC review workflow ( 42 ). Finally, the reduction of follow-up appointments, improved allocation of tasks and shift to remote care following VFC review suggests a concomitant cost reduction.…”
Section: Discussionmentioning
confidence: 75%